As you like it A Shakespeare children's story - Shakespeare, William (Sweet cherry USA, 2013)
(3z(BAll the world$1 (Bs a stage...(3y (BOne of the most quoted lines of Shakespeare was first heard in this play. As You Like It is set in the enchanted Forest of Arden, where Rosalind, the daughter of an exiled duke, and Orlando, the son of one of her father$1 (Bs courtiers, become entangled in a game of love and mistaken identity.s
shelving location "L"
Keywords: text,English